Erratum to: An International Urogynecological Association (IUGA) / International Continence Society (ICS) joint report on the terminology for female pelvic organ prolapse (POP). Issue 4 (April 2016) - Haylen, Bernard; Maher, Christopher; Barber, Matthew; Camargo, Sérgio; Dandolu, Vani; Digesu, Alex; Goldman, Howard; Huser, Martin; Milani, Alfredo; Moran, Paul; Schaer, Gabriel.; Withagen, Mariëlla
Abstract Introduction The terminology for female pelvic floor prolapse (POP) should be defined and organized in a clinically-based consensus Report. Methods This Report combines the input of members of two International Organizations, the International Urogynecological Association (IUGA) and the International Continence Society (ICS), assisted at intervals by external referees. Appropriate core clinical categories and a sub-classification were developed to give a coding to definitions. An extensive process of fourteen rounds of internal and external review was involved to exhaustively examine each definition, with decision-making by collective opinion (consensus). Results A Terminology Report for female POP, encompassing over 230 separate definitions, has been developed. It is clinically-based with the most common diagnoses defined. Clarity and user-friendliness have been key aims to make it interpretable by practitioners and trainees in all the different specialty groups involved in female pelvic floor dysfunction and POP. Female-specific imaging (ultrasound, radiology and MRI) and conservative and surgical managements are major additions and appropriate figures have been included to supplement and clarify the text. Emerging concepts and measurements, in use in the literature and offering further research potential, but requiring further validation, have been included as an appendix. Interval (5–10 year) review is anticipated to keep the document updated and as widely acceptable as possible. Conclusion A consensus-based Terminology Report for female POP has been produced to aid clinical practice and research.